Chocolate Consumption and Risk of Heart Failure: A Meta-Analysis of Prospective Studies - Gong, Fei (Nutrients, 2017)
Epidemiological studies have shown inconsistent findings on the association between chocolate consumption and risk of heart failure (HF). We, therefore, performed a meta-analysis of prospective studies to determine the role of chocolate intake in the prevention of HF. We searched databases of PubMed, Web of Science, and Scopus through December 2016 and scrutinized the reference lists of relevant literatures to identify eligible studies. Study-specific hazard ratios (HRs) and 95% confidence intervals (CIs) were aggregated using random effect models. The dose–response relationship between chocolate consumption and incident HF was also assessed. This meta-analysis is registered with PROSPERO, number CRD42017054230. Five prospective studies with 106,109 participants were finally included. Compared to no consumption of chocolate, the pooled HRs (95% CIs) of HF were 0.86 (0.82–0.91) for low-to-moderate consumption (<7 servings/week) and 0.94 (0.80–1.09) for high consumption (≥7 servings/week). In dose–response meta-analysis, we detected a curve linear relationship between chocolate consumption and risk of HF (p for nonlinearity = 0.005). Compared with non-consumption, the HRs (95% CIs) of HF across chocolate consumption levels were 0.92 (0.88–0.97), 0.86 (0.78–0.94), 0.93 (0.85–1.03), and 1.07 (0.92–1.23) for 1, 3, 7, and 10 servings/week, respectively. In conclusion, chocolate consumption in moderation may be associated with a decreased risk of HF.